Natural Disaster Risk Assessments for Pine Honey Apiaries in Muğla, Turkey - Fatih Sarı (Doğal Afetler ve Çevre Dergisi)
Since Muğla province has 90% of the world's total pine honey production, ensuring efficiency and economic income requires the determination of measures for apiary locations and estimation of risks. However, ensuring development and productivity requires identifying natural disasters susceptibility such as forest fires and floods to maintain productivity. Muğla province has a high forest fire potential due to its dense forest cover and approximately 200 forest fires occur each year. Forest fires are one of the main factors that threaten apiaries, as there are a lot of apiary places (approximately 15,000) in forests for pine honey. On the other hand, due to the mountainous topography and high precipitation rate of Muğla, the province has a high rate of flood formation (20 per year), which threatens the hive sites by destroying the entire colony. In this study, Apiary Locations Risk Index (ALRI) was carried out to guide the insurance process for apiary locations by applying the Forest Fire Risk Index (FFRI) and the Flood Hazard Risk Index (FHRI). Determination of forest fire risk zones and flood hazard maps requires environmental, forestry, topographic, economic and meteorological parameters to be handled within a decision support platform. For this purpose, Analytical Hierarchy Process (AHP) technique supported by Geographic Information System (GIS) was used in the creation of sensitivity maps. As a result, 1533.40 ha (11.82%) of the study area was determined as extremely risky areas for apiary areas. The results were confirmed with 1454 forest fire sites and 20 flood hazard sites where the Eşen, Dalaman, Çine, Sarıçay, Akçay, Kamiişdere and Namnam rivers were stated to be highly susceptible to flood hazard.